Cybercrime and society - Yar, Majid (Los Angeles, California : Sage, 2013)
Providing a clear and systematic introduction to current debates surrounding cybercrime, this text looks at a range of issues including computer hacking, cyber-terrorism, media 'piracy' and online stalking.
Cybercrime and the Internet: an introduction -- Hackers, crackers and viral coders -- Political hacking: from hacktivism to cyberterrorism -- Virtual 'pirates': intellectual property theft online -- Cyber-frauds, scams and cons -- Illegal, harmful and offensive content online: from hate speech to 'the dangers' of pornography -- Child pornography and child sex abuse imagery -- The victimization of individuals online: cyberstalking and paedophilia -- Policing the internet -- Cybercrimes and cyberliberties: surveillance, privacy and crime control.
Includes bibliographical references and index.
Keywords: COMPUTER CRIMES